Bending properties of steel faced sandwich composite panels with phenolic foam cores. (May 2016) - Tang, Zhirong; Zha, Xiaoxiong; Zu, Dequan
This paper investigates the mechanical properties of a new type of sandwich composite panel composed of two steel faces and a phenolic foam core under uniformly distributed load. Two groups of full-scale phenolic foam sandwich panels, which are classified as thin faced wall panels and thick faced roof panels, are tested by vacuum chamber loading method. The general formulae for calculating deformation and load bearing capacity are derived from the force-deformation relationships of differential equations, where the calculation of thin faced sandwich panels can be regarded as a special case of thick faced sandwich panels. Based on these formulae, the bending moment partition coefficient and shear partition coefficient are given for simplified calculation in design. The finite element method with software ABAQUS is used to verify the results from theoretical formulae and tests. By comparing these results, a good agreement is obtained. The sensitivity analyses show that the thin faced wall panels are very sensitive to initial geometrical imperfection, whereas the thick faced roof panels are not.